Evaluasi Sistem Informasi Manajemen Pembuatan KTP Elektronik Dalam Mendukung Administrasi Kependudukan Di Kecamatan Batang Hari Leko Kabupaten Musi Banyuasin - Tores, Ropal (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine the evaluation of management information systems in support of the Electronic Identity Card (E-KTP) administration of residence in the district of Batang Hari Leko. This study was done using two methods: 1). Field research that the researcher visited head office of sub-district Batang Hari Leko by a question and answer directly to the employees who have the authority to provide the data and information required. 2). Library Research that the data collection conducted by researchers with a way to read all the reference books that relate to the title and the problems observed in order to obtain theories that can be used as a material of data analysis tools available. The results showed that the evaluation of the management information system of Electronic Identity Card (E-KTP) proven to support the administration of residence in the district of Batang Leko, all that can be seen from the simple process of making Electronic Identity Card (E-KTP), surveillance systems that have a connection of integrated which is equipped with a special chip that does not allow longer exists citizens who have dual identity card, the device information management system which is used for the manufacture of Electronic Identity Card (E-KTP) that has an integrated connection in every part, and requirement of making Electronic Identity Card (E-KTP) is very easy so as to realize the effective and efficient services to the public. This study provides the latest evidence regarding the evaluation of management information systems in support of the Electronic Identity Card (E-KTP) administration of residence in the district of Batang Hari Leko.